Flow around cylindrical, rectangular and square bluff bodies / L.S. Kit, M. Govarhan and Mohd Kamel Wan Ibrahim - Kit, L.S; Govarhan, M.; Wan Ibrahim, Mohd Kamel (2006)
The flow around a bluff body is of great interesting engineering practice. Typical example of engineering applications is the computation of wind load on building and simulations of the flow around vehicles. This work is connected to the latter and studies some aspects related to vehicle and aircraft aerodynamics. such as drag and lift. Most studies of this kind of flow are experimental. The main objectives of conducting this research are to gain better understanding of flow through various bluff bodies. The bluff bodies that were used in this experiment are the cylindrical rods and the square rods. The dimensions are 20 mm in diameter and 100 mm long for the cylindrical rods and 20 x 20 mm wide and 100 mm long for the square rods. These cylindrical and square rods are then placed in a water stream with flat surface on its bottom of a hydraulic bench of 180 x 250 x 700 mm in dimensions. Water is pumped from one end of the stream flows out at the other end creating a flow of water along the stream. Various combinations like side by side and tandem arrangements of the bluff bodies were tried and for each arrangement the visualization studies were conducted. Then, aluminum powder sprayed on the surface of the water to visualize the flow pattern while passing over the Bluff bodies. A high resolution digital camera was mounted on the top of the water stream to capture the flow pattern created by the aluminum powder at surface of the water. The results are then studied analysed. The results indicated the formation of vortices, separation lines with distinct patterns depending on the configuration under study.